The Epidemiological Boehringer Ingelheim Employee Study (Part 3): Association of Elevated Fasting Insulin Levels but Not HOMA-IR With Increased Intima Media Thickness and Arteriosclerosis in Middle-Aged Persons - Röhling, Martin; Kempf, Kerstin; Kolb, Hubert; Martin, Tobias; Schneider, Michael; Martin, Stephan (Frontiers in Cardiovascular Medicine, 2021)
Background: Recently published genetic studies have indicated a causal link between elevated insulin levels and cardiovascular disease (CVD) risk. We, therefore, hypothesized that increased fasting insulin levels are also associated with precursors of CVD such as endothelial lesions. Methods: Middle-aged (≥40 years, n=1639) employees were followed up for the occurrence of increased intima media thickness (IMT ≥1mm) or plaques in abdominal or cervical arteries (arteriosclerosis). Multivariable logistic regression analyses determined the incidence of increased IMT or arteriosclerosis. Adjusted relative risk (ARR) for increased IMT and arteriosclerosis was calculated by using Mantel-Haenszel analysis. Results: Increased IMT was diagnosed in 238 participants (15 %) and 328 (20 %) developed arteriosclerosis after 5 years of follow-up. Logistic regression analysis identified fasting insulin, BMI and smoking as risk factors for both cardiovascular endpoints (all p<0.05), whereas age and diastolic blood pressure were risk factors for increased IMT only, and male sex was associated with incident arteriosclerosis only (all p<0.01). Additional adjustment for BMI change during follow-up did not modify these associations (including fasting insulin), but adjustment for fasting insulin change during follow-up removed BMI as risk factor for both cardiovascular endpoints. Fasting insulin change during follow-up but not BMI change associated with increased IMT and arteriosclerosis (both p<0.001). ARR analysis indicated that high fasting insulin and BMI added to age and sex as risk factors. Homeostatic model assessment of insulin resistance (HOMA-IR) did not associate with either cardiovascular endpoint in any model and smoking did not increase the risk conferred by high fasting insulin levels. Conclusions: Higher fasting insulin levels and increases in fasting insulin over time are associated with atherogenic progression and supersede BMI as well as HOMA-IR as risk factors.